PREVALENCE OF OVERWEIGHT AND OBESITY IN A ROMA POPULATION FROM SOUTHERN ROMANIA - CALARASI COUNTY - Enache, G. (Acta Endocrinol (Buchar), 2018)
INTRODUCTION: The prevalence of obesity has reached alarming levels in the European Union, including in Romania. Data on the prevalence of obesity is only available at the national populational level, but this may hide the increased levels in disadvantaged groups. The purpose of this study was to evaluate the prevalence of overweight and obesity in the Roma population in Southern Romania. MATERIAL AND METHOD: This cross-sectional, epidemiological, non-interventional study was conducted from March 2014 to May 2017 in several settlements from Calarasi County. Screening procedures included interviews about medical history, lifestyle, anthropometric and clinical measurements and fasting capillary glucose. RESULTS: The study population consisted of 1120 adult subjects, of which 735 Roma. In Roma population group, the prevalence of underweight, normal weight, overweight and obesity was 4.5% (n=33), 25% (n=184), 25.3% (n=186) and 45.2% (n=332) respectively. In Romanian Caucasians group, the prevalence of underweight, normal weight, overweight and obesity was 2.3% (n=9), 20% (n=77), 33.8% (n=130) and 43.9% (n=169) respectively. Among the Romanian Caucasians significant predictors of obesity were a sedentary lifestyle and current smoking. The odds of being obese in Roma population were higher in sedentary lifestyle persons and lower in current smokers, with primary education, and in those living in rural settlements. The family history of obesity had a significant association with obesity only in Roma population. CONCLUSIONS: Our results confirm the need to implement prevention programs in high-risk populations due to the double burden of malnutrition, lack of medical education and preventive healthcare, low socio-economic level.